2012
DOI: 10.3109/08958378.2012.716869
|View full text |Cite
|
Sign up to set email alerts
|

Subacute inhalation toxicity assessment of fly ash from industrial waste incinerators

Abstract: Fly ash from industrial waste incinerators has been a significant concern because of their constituent toxic heavy metals and organic compounds. The objective of this study was to identify the subacute inhalation toxicity of fly ash from industrial waste incinerators, using whole body inhalation exposure chambers. Male and female groups of Sprague-Dawley rats were exposed to fly ash by inhalation of concentrations of 0, 50, 100, 200 mg/m(3), for 6 h/day, 5 days/week for 4 weeks. There was no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…We observed that the exposed population had slightly higher monocyte values than the controls, but also generally lower monocyte values (monocytopenia). An experimental study on rats exposed to fly ash from incinerators also showed a significant increase in monocyte counts in these rats [39]. In addition, a community-based study in China on outdoor air pollution and white blood cells revealed that the value of monocytes might be a function of the chemical nature of the particles [40].…”
Section: Discussionmentioning
confidence: 95%
“…We observed that the exposed population had slightly higher monocyte values than the controls, but also generally lower monocyte values (monocytopenia). An experimental study on rats exposed to fly ash from incinerators also showed a significant increase in monocyte counts in these rats [39]. In addition, a community-based study in China on outdoor air pollution and white blood cells revealed that the value of monocytes might be a function of the chemical nature of the particles [40].…”
Section: Discussionmentioning
confidence: 95%
“…The small respirable particles of fly ash are easily inhaled to the lungs, where the harmful condensed phases are extracted by body fluids and thereby pose a health hazard (Lauf, 1985;Nakane, 2012;Shim et al, 2012). At disposal in landfills and ash ponds, once exposed to moisture, leaching from the ash will occur and provide a pathway for toxic compounds to reach groundwater supplies (Jianguo and Wei, 1998;Jianguo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%